Transformasi Pariwisata Berbasis Ekosistem Lintas Sektor: Model Pengembangan dan Penilaian Daya Tarik Ekosistem Pariwisata di Pantai Kairatu, Maluku - Wali, Berlin; Afdhal, Afdhal (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This study aims to develop strategic guidelines to enhance the efficiency of tourism potential utilization in the formation of a tourism ecosystem at Kairatu Beach, West Seram Regency, Maluku Province. The concept of a regional tourism ecosystem is examined by emphasizing the involvement of various actors, including government authorities and the business sector, in the management and development of tourist destinations. This research employs an ecosystem-based tourism attractiveness assessment approach, integrating key performance indicator evaluations to assess a region's tourism potential. The algorithm developed in this study enables data-driven assessment to understand the competitiveness and sustainability of the tourism ecosystem. The analysis results indicate that the regional tourism industry and its value chain can be interpreted as an ecosystem consisting of interrelated elements. Several development strategies are identified, including institutional strategies, business image, cultural and educational initiatives, as well as innovation and technology, all of which play a role in directing the development of Kairatu Beach’s tourism potential. These findings offer a novel perspective on understanding cross-sectoral tourism ecosystems at the regional level and provide recommendations for the development of social and political sciences, particularly in formulating ecosystem-based tourism policies. The practical implications of this study serve as a foundation for stakeholders in designing more effective, sustainable, and cross-sectorally synergized tourism management and development strategies.